2019
DOI: 10.1542/hpeds.2018-0168
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Medication Prescribing Patterns in Pediatrics: An Update

Abstract: A B S T R A C TOBJECTIVES: To describe the frequency of off-label drug use in 2014 as defined by the Food and Drug Administration (FDA)-approved age ranges in patients #18 years of age, to determine the rate of off-label drug use in 2014 by drug classification, and to compare current off-label medication usage rates with historical rates.METHODS: This is a retrospective cohort study of an administrative database containing inpatient resource use data from January 1, 2014, to December 31, 2014. Patients #18 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 24 publications
1
45
0
6
Order By: Relevance
“…Additionally, it has been shown that younger children tend to have a stronger placebo response than older children . This would make it especially difficult to demonstrate efficacy in younger children, which is problematic considering that the off‐label drug use is highest in children in the first year of life …”
Section: Applications Of Machine Learning In Pediatricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been shown that younger children tend to have a stronger placebo response than older children . This would make it especially difficult to demonstrate efficacy in younger children, which is problematic considering that the off‐label drug use is highest in children in the first year of life …”
Section: Applications Of Machine Learning In Pediatricsmentioning
confidence: 99%
“…63 This would make it especially difficult to demonstrate efficacy in younger children, which is problematic considering that the off-label drug use is highest in children in the first year of life. 11 One way to limit the impact of placebo response on trial outcomes would be to identify baseline predictors of placebo response so that trials can be enriched prerandomization with subjects that are less likely to respond strongly to placebo. 8 This strategy has been used in pediatric trials, resulting, for example, in the successful application for a pediatric indication of rizatriptan for acute…”
Section: Predicting Treatment Respondersmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of self‐medication, off‐label, is even higher, with over‐the‐counter and complementary medicines use in pregnancy ranging between 25% and 68% . In 2014, the frequency of paediatric off‐label prescribing in the US ranged from 45.5% to 54.2% . European studies in 2017 showed that between 2% and 100% of children in an outpatient setting and up to 74% of pregnant women received medicines off‐label .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In 2014, the frequency of paediatric off-label prescribing in the US ranged from 45.5% to 54.2%. 8 European studies in 2017 showed that between 2% and 100% of children in an outpatient setting and up to 74% of pregnant women received medicines off-label. 9 The Australian experience of off-label (34%-95.6%) and unlicensed (5.7%-34.6%) medicines use in neonatal intensive care varies, with 44%-100% of all neonates administered at least one such medicine during their hospital stay.…”
Section: Introductionmentioning
confidence: 99%